Aspectos clínicos e moleculares da dengue na epidemia de 2012/ 2013 em Goiânia – GO, Brasil. - Rocha, Benigno Alberto Moraes da (2015)
Background: Dengue is the fastest growing arbovirosis in the world, infecting almost 390 million people. The dengue virus is the etiological agent of the disease, which has four serotypes (DENV1-4). All serotypes can cause dengue, varying from asymptomatic to severe forms and may lead to death. In Brazil, in 2010, there was the re-emergence of serotype DENV-4 after 28 years. In 2013, it was registered the largest epidemic in history with more than 1.4 million cases and circulation of the four serotypes. In the state of Goiás, Central Region of Brazil, after serotype DENV-4 entry in 2011, for the first time in the region, in 2013, there was a major epidemic which registered more than 10% of the cases in Brazil, more often DENV -4 followed by DENV-1. In this scenario, a study was conducted with the objective to characterize the clinical and molecular profile of patients with dengue; establish if there were associations between clinical and laboratory markers of severity with the infectious virus serotypes; and genetic characterization of the more frequent virus serotype during the 2012/2013 dengue epidemic in Goiânia, Goiás. Methods: A prospective clinical study with suspected dengue patients from eight reference health units (five public, two hospitals and three of secondary level; and three private hospitals) from January 2012 to July 2013 was conducted. The patients were evaluated in three different moments by clinicians who collected clinical and sociodemographic information. Blood sampling for laboratory testing (Hg, AST, and ALT) and confirmatory tests for dengue infection (IgM, IgG, NS1, and RT-PCR) were performed. The gene sequencing of dengue virus type 4 envelope was also carried out. Patients with confirmation of dengue infection were classified according to clinical signs according to the World Health Organization. Principal findings: Six hundred and fifty patients were recruited; 18 were excluded, and 632 were followed. Four hundred fifty-two patients (71.5%) had confirmed infection and 112 (24.8%) were hospitalized. More than 90% were over 15 years of age, and 235 were female (52.0%). In 328 patients, it was possible to classify the type of infection, and 248 (75.6%) of these had a secondary infection. 188 (41.6%) were classified as FD, 238 (52.6%) as DwC and 26 (5.8%) with DG. Compared to those aged xvi over 15 years, spontaneous bleeding, severe abdominal pain and plasma extravasation were more frequent in children under 15 years of age (p <0.05). There was one death of a 16-year-old. During two years of follow-up, viral RNA was identified in 243 (40.5%) of 600 patients evaluated in these tests, where the four serotypes were identified: 91 (37.4%) with DENV-1, 4 (1.6%) with DENV-2, 13 (5.3%) with DENV-3 and 135 (55.5%) with DENV-4. A higher frequency of some symptoms of severity was observed (thrombocytopenia, spontaneous bleeding and severe abdominal pain) in DENV-1 serotype compared to DENV-4. Eighty percent of patients with DENV-4 had a secondary infection. In the phylogenetic study of DENV-4 envelope gene, genotype II was identified. Conclusion: The present study described clinically and molecularly a large dengue epidemic that occurred in a state of Brazil's Central Region, which revealed the concurrent circulation of the four serotypes, the frequency of clinical signs of disease severity in children aged under 15 years and in people with DENV-1 infection. It also identified the current genotype of the most common serotype in the epidemic. These findings should serve as a warning sign for the health authorities because we are experiencing a significant dispersion of serotypes situation worldwide.